Pengaruh Pijat (Massage) terhadap Perubahan Intensitas Nyeri Rematik pada Lansia di Desa Kertapati Puskesmas Dusun Curup Bengkulu Utara - Marlena, Feny; Juniarti, Rita (Program Studi Ilmu Keperawatan, Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2019)
The purpose of this study was to determine the effect of massage on the intensity of rheumatic pain in the elderly in the village of Kertapati, Puskesmas, Dusun Curup, North Bengkulu. This research is a quantitative study using a quasi experimental research design with pre and post test design research designs. The sample in this study amounted to 10 people taken by purposive sampling technique. The analysis used is univariate analysis and bivariate analysis, the statistical test used is the t-dependent test. The results of the study, the average value of rheumatic pain before a massage intervention (massage) in the elderly in the village of Kertapati, Curup Hamlet North Bengkulu is 5.2 and after the intervention is 3.4. T-dependent test results found that there were significant differences in the value of pain before and after massage intervention (massage) with a value of 0,000. In conclusion, there is an effect of massage on the intensity of rheumatic pain in the elderly in the village of Kertapati, Puskesmas, Dusun Curup, North Bengkulu. It is expected to provide optimal nursing care, especially massage interventions to the elderly and can socialize massage skills to the elderly, so that they can independently massage when there is a pain attack.Keywords: Elderly, Rheumatic Pain, Massage